1992
DOI: 10.1007/bf02447481
|View full text |Cite
|
Sign up to set email alerts
|

The use of image analysis for spore counts of white-rot fungi

Abstract: SUMMARYAn improved method has been developed for the determination of fungal spore counts using a haemocytometer. The method uses a personal computer with a frame grabber card and commercial imaging software. Semi-automation using an iterative programming technique was implemented to count the spores produced by Phanerochaete chrysosporium. Rapid and reliable counts were achieved using image processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It only considers those connections that minimize the total length across the graph (Figure 1C; Prim, 1957). MST has a long history of application in biology and ecology to describe various spatial patterns (Dussert et al, 1986(Dussert et al, , 1987Cantwell and Forman, 1993;Lockwood et al, 1993;Jones et al, 1996;Keitt et al, 1997;Wallet and Dussert, 1997;Bunn et al, 2000, Urban andKeitt, 2001;Labra et al, 2005). However, to fully describe the invasion process, the MST should be rooted at the first recorded invasion site and directed to reflect the temporal sequence of site invasion.…”
Section: Introductionmentioning
confidence: 99%
“…It only considers those connections that minimize the total length across the graph (Figure 1C; Prim, 1957). MST has a long history of application in biology and ecology to describe various spatial patterns (Dussert et al, 1986(Dussert et al, , 1987Cantwell and Forman, 1993;Lockwood et al, 1993;Jones et al, 1996;Keitt et al, 1997;Wallet and Dussert, 1997;Bunn et al, 2000, Urban andKeitt, 2001;Labra et al, 2005). However, to fully describe the invasion process, the MST should be rooted at the first recorded invasion site and directed to reflect the temporal sequence of site invasion.…”
Section: Introductionmentioning
confidence: 99%
“…In Jones et al. ( 1992 ), local threshold and morphological transformation are used to calculate spore numbers accurately. Red and blue signals are sampled for pixel segmentation.…”
Section: Other Microorganism Counting Methodsmentioning
confidence: 99%
“…( 1995 ) Heterotrophic bacteria Edge strength filter, minimum and maximum cell size filter and Marr-Hildeth method Jones et al. ( 1992 ) Spores RGB processing Local thresholding and morphological transform Zalewski and Buchholz ( 1996 ) Yeast cells Color filtering and contour enhancement Thresholding Shabtai et al. ( 1996 ) Fungi Self-organizing multilayer neural network Akiba and Kakui ( 1997 ) Plankton Local auto-correlational masks PCA Auto-correlational masks and discrimination analysis 90% accuracy Robinson et al.…”
Section: Other Microorganism Counting Methodsmentioning
confidence: 99%
“…Billon et al [185] have monitored the germination of single spores of Clostridium botulinum by observing them with a phase-contrast microscope and simply recording the change in refractivity. Jones et al [186] have observed also a change in refractivity when they developed their automated method for Phanerochaete chrysosporium, but they have suggested it may be due to water evaporation. Recombinant bacteria such as E. coli can store the foreign proteins they produce as inclusion bodies [53,187] or crystals [188] which do not refract light as the rest of the cell.…”
Section: ) Pellet Convex Area -Core Convex Areamentioning
confidence: 97%